1996
DOI: 10.1111/j.1365-246x.1996.tb05267.x
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional magnetotelluric inversion assuming Gaussian static shift

Abstract: A data-adaptive 2-D inversion scheme for magnetotelluric data, which simultaneously finds the smoothest model with the smallest misfit whilst solving for galvanic static shift parameters, is described. Trade-off parameters between data misfit, model roughness, and static shift norm are determined so as t o maximize the likelihood of the data on the assumption that static shifts have Gaussian distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(87 citation statements)
references
References 15 publications
(20 reference statements)
1
85
0
Order By: Relevance
“…de Groot-Hedlin (1991) suggested that static shifts may be treated as unknown free parameters during inversion. Also, Gaussian distributions of the static shifts (Ogawa and Uchida, 1996) are assumed. This is a very simple, but reasonable assumption because the static shifts in the data are assumed normally distributed and these distributions have a central mean and well-estimated variance.…”
Section: Mt Data Acquisition and Processingmentioning
confidence: 99%
“…de Groot-Hedlin (1991) suggested that static shifts may be treated as unknown free parameters during inversion. Also, Gaussian distributions of the static shifts (Ogawa and Uchida, 1996) are assumed. This is a very simple, but reasonable assumption because the static shifts in the data are assumed normally distributed and these distributions have a central mean and well-estimated variance.…”
Section: Mt Data Acquisition and Processingmentioning
confidence: 99%
“…In this study, a two-dimensional inversion was conducted with two types of constraints similar to Ogawa and Uchida (1996). One type is model roughness norm, and the other is static shift L2 norm.…”
Section: Resultsmentioning
confidence: 99%
“…A two-dimensional inversion was applied to the TM mode data (Z.,,y), based on the work of Ogawa and Uchida (1996) and Ogawa (1997). An outline of the idea is described below.…”
Section: Two-dimensional Inversion Schemementioning
confidence: 99%
See 1 more Smart Citation
“…We included static shifts as model parameters in addition to the model resistivity (Ogawa and Uchida, 1996). The misfit was minimized under the two constraints; one is the Laplacian model roughness and the other is static shift L2 norm.…”
Section: Two-dimensional Modelingmentioning
confidence: 99%